IMPROVING PROFESSIONAL COMPETENCE AND KNOWLEDGE SHARING BASED ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR TOWARD HUMAN RESOURCES PERFORMANCE - Agustina Maulidatur Rika; Tatiek Nurhayati (IJIBE (International Journal of Islamic Business Ethics), 2017)
This study aims to describe and analyze the effect of organizational citizenship behavior on HR performance with professional commitment and knowledge sharing as an intervening variable. The population used is the total number of employees of local water company (PDAM) Semarang total of them are 569 people, with a total sample of 85 people. The sampling technique is Proportional Random Sampling. The analysis tool is Partial Least Square. Another test result shows that OCB has a positive effect on professional competence. The test proves that OCB and professional competencies have a positive effect on knowledge sharing. Organizational citizenship behavior, professional competence and knowledge sharing have a positive effect on HR performance. The test results show that professional competence is able to be an intervening variable between OCB and knowledge sharing, while professional competence is not able to be an intervening variable between OCB and HR performance. Knowladge sharing is able to be an intervening variable between OCB and HR performance and knowledge sharing can also be an intervening variable between professional competence and HR performance.Keywords:    Organizational citizenship behavior, professional commitment and knowledge sharing and performance of Human Resources